Gravitational Properties of Atom - Orlov, S. (International Journal of Scientific Research in Civil Engineering, 2018)
The evidence that the strength of anybody provide nuclear forces of gravity. The nuclear force of gravity generated by the essential micro vortices. The vortex creates a pressure gradient in the ether. The pressure gradient is the source of nuclear energy. The nuclear force of gravity on the surface of the cores is equal for all elementary particles.
Keywords: Theory of atomic vortex gravitation; cosmology and cosmogony; Strength; mass and energy substances